Case report: The first description of a Dieulafoy's lesion in the gastric mucosa of a dog - Barrantes Murillo, Daniel Felipe; Tillson, Michael; Koehler, Jennifer W.; Sandey, Maninder (Frontiers in Veterinary Science, 2022)
An approximately 12-year-old, 31 kg, male neutered Labrador retriever was presented to the referring hospital with an acute onset (less than one day) of hematemesis and melena. The dog was treated supportively for a presumptive gastric ulcer for four days with intravenous fluids, gastro protectants including pantoprazole, misoprostol, sucralfate, and barium, as well as an anti-emetic (maropitant) and analgesics (fentanyl, gabapentin, and tramadol). Throughout medical management, the dog continued to require blood transfusions approximately every 24 hours. Given the poor medical response, the patient was subjected to an exploratory laparotomy. During surgery, a grossly raised, blister-like lesion on the mucosal surface of the stomach was appreciated on the lesser curvature of the stomach. A partial gastrectomy was performed, and the segment was submitted for histological evaluation. Histologically, there were multiple, tortuous, medium-caliber muscular arteries (>1.0 mm in diameter) in the submucosa. A single large-caliber artery (>0.75 mm in diameter) containing a partially occlusive thrombus extruded through the mucosa and projected on the ulcerated surface. The patient's signs were similar clinically and histopathologically to Dieulafoy's lesion in people. Dieulafoy's lesion is a potentially life-threatening disorder that causes gastrointestinal hemorrhage. This lesion is characterized by a dilated, large-caliber, aberrant submucosal artery that erodes through the epithelium and ruptures, resulting in massive and potentially fatal hemorrhage. This lesion has never been documented previously in a dog.